Uniqueness as Human Beings - Chackalackal, Saju (Journal of Dharma, 2003)
Our uniqueness as human beings does not consist merely in possessing a rational nature, but in constantly and consciously exercising it in order to arrive at intelligent decisions and ensuing actions. This gives a humane face to whatever we are and whatever we do. Indeed, it is characteristic of our nature that we are able to meaningfully modify our responses taking into account the things and events in and around our lives. It is not a one-time action, but an all-encompassing and ever-continuous phenomenon covering every moment and dimension of human life, pointing to the dynamism that is integral to our nature.